Mechanisms and Therapeutic Strategies of Macrophage Polarization in Intervertebral Disc Degeneration - Kaiyuan Zheng; Siyu Wang; Meng Deng; Yaomin Luo; Wen Li; Lianlin Zeng; Yinxu Wang (JOR Spine)
ABSTRACT Background Intervertebral disc degeneration (IVDD) is a leading cause of low back pain (LBP), contributing significantly to global disability and productivity loss. Its pathogenesis involves complex processes, including inflammation, cellular senescence, angiogenesis, fibrosis, neural ingrowth, and sensitization. Emerging evidence highlights macrophages as central immune regulators infiltrating degenerated discs, with macrophage polarization implicated in IVDD progression. However, the mechanisms linking macrophage polarization to IVDD pathology remain poorly elucidated. Methods A comprehensive literature review was conducted by searching major databases (PubMed, Web of Science, and Scopus) for studies published in the last decade (2014–2024). Keywords included “intervertebral disc degeneration,” “macrophage polarization,” “inflammation,” “senescence,” and “therapeutic strategies.” Relevant articles were selected, analyzed, and synthesized to evaluate the role of macrophage polarization in IVDD. Results Macrophage polarization dynamically influences IVDD through multiple pathways. Pro‐inflammatory M1 macrophages exacerbate disc degeneration by amplifying inflammatory cytokines (e.g., TNF‐α, IL‐1β), promoting cellular senescence, and stimulating abnormal angiogenesis and neural ingrowth. In contrast, anti‐inflammatory M2 macrophages may mitigate degeneration by suppressing inflammation and enhancing tissue repair. Therapeutic strategies targeting macrophage polarization include pharmacological agents (e.g., cytokines, small‐molecule inhibitors), biologic therapies, gene editing, and physical interventions. Challenges persist, such as incomplete understanding of polarization triggers, lack of targeted delivery systems, and limited translational success in preclinical models. Conclusion Macrophage polarization is a pivotal regulator of IVDD pathology, offering promising therapeutic targets. Future research should focus on elucidating polarization mechanisms, optimizing spatiotemporal control of macrophage phenotypes, and developing personalized therapies. Addressing these challenges may advance innovative strategies to halt or reverse IVDD progression, ultimately improving clinical outcomes for LBP patients.